Crossing Boundaries in Graphic Narrative: Essays on Forms, Series and Genres - Jakaitis, Jake and Wurtz, James F. (EBL-Schweitzer, 2012)
Cover; Table of Contents; Introduction; Part I: Ways of Reading; 1. Michael Chabon's Amazing Adventures with Dark Horse Comics; 2. The Comic Modernism of George Herriman; 3. Fantastic Alterities and The Sandman; 4. Thirty-Two Floors of Disruption; Part II: Reading Ethnicity; 5. Picturing Books; 6. Iconoclastic Readings and Self-Reflexive Rebellions in Marjane Satrapi's Persepolis and Persepolis 2; 7. Drawing the Trauma of Race; 8. Mezclando (Mixing) the "Facts" and the Power of the Image in Latino USA; Part III: Reading the Hero; 9. "3X2(9YZ)4A"; 10. My Wonder Woman; 11. Paneling Rage
https://katalog.adlr.link/Record/0-1653658045